Monosodium glutamate restricts the adipogenic potential of 3T3‐L1 preadipocytes through mitotic clonal expansion - Türküner, Mehmet Soner; Özcan, Ferruh (Cell biology international, 2020)
Recent epidemiologic studies pointed out a significant correlation between dietary monosodium glutamate (MSG) and increased body mass index. Corroborating evidences came from animal studies depicting a clear association between dietary MSG intake and increased abdominal fat, dyslipidemia, adipocyte hypertrophy, and total body weight gain. Taken together with the inferred absence of conspicuous hypothalamic neuropathies the hallmark of disease etiopathogenesis in MSG‐obese animals, these animal studies with dietary MSG strongly argue for the presence of an alternative non‐neuronal route for MSG to mediate its adipose tissue‐specific phenotype and body weight gain. On the basis of this hypothesis, we investigated the direct effect of physiologically relevant low (100 µM), moderate (250 µM), and high dosages (2.5 and 25 mM) of MSG on distinct phases of adipocyte differentiation. MSG‐dependent changes in cell proliferation and lipid accumulation were analyzed by cell proliferation assays, flow cytometry, and biochemical methods, respectively. Physiologically relevant high dosages MSG demonstrated a significant potential in reducing MCE and thereof adipogenic capacity of preadipocytes in a dose‐dependent manner by restricting the availability of critical mitogenic proteins, CCAAT/enhancer‐binding protein β (CEBPβ), and the mitotic cyclin B. Our findings warrant further investigations to unravel the effect of long‐term dietary MSG intake on capacity of preadipocytes in different fat depots to undergo mitotic clonal expansion and hyperplasia in rodent models and human subjects, respectively.